Determinants of Stunting Among Children Under Two Years of Age in Batu Bara District, Indonesia - Ivan Elisabeth Purba; Leli Mariani Harahap; Rinawati Sembiring; Toni Wandra; Donal Nababan (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Batubara District is one of 33 districts/cities in North Sumatra Province with relatively high stunting prevalence. This study aimed to determine the determinants of stunting among children under two years of age in the Laut Tador Health Center work area of Batu Bara District in 2023. The design of this study was case-control. The number of samples was 154 (case), and control was 154 (non-stunting). Respondents were mothers of children under two years of age. Independent variables were chosen based on the preliminary study results in the study area, including the mother's education, mother's knowledge, family income, history of mother on ANC visits, history of mother taking iron tablets, history of child getting exclusive breastfeeding, and history of child getting complementary feeding. Trained health workers and members of the researcher team collected all data. Analysis data included univariate, bivariate analysis using chi-square and multivariate (logistic regression) analysis. The study showed that there were significant differences between family income (p < 0.001), history of mother on ANC visits (p < 0,001), history of a mother taking iron tablets (p=0.043), history of children under two years getting exclusive breastfeeding   (p < 0.001), and history of children under two years of getting complementary feeding  (p < 0.001) and stunting, respectively. The role of health posts (Posyandu) and village cadres should be improved to provide information about antenatal care, taking iron tablets during pregnancy, exclusive breastfeeding, and complementary feeding to pregnant women, including monitoring children's growth.